Long Range Dependence and Market Efficiency: Evidence From the Indian Stock Market - Parthasarathy, Srikanth (Indian Journal of Finance, 2013)
This empirical investigation examines the long memory or long range dependence in the Indian stock market vis-Ã -vis market efficiency. The researcher examined the daily data of the major indices and large, liquid common stocks using the Rescaled range (R/S) analysis to measure the Hurst exponent using both static and dynamic approach. The researcher evidences significant long range dependence in all the tested indices and many individual stocks. The results are not consistent with weak form efficiency in the Indian stock market. The dynamic approach evidences time dependence and rejects both the notion of evolving efficiency through the passage of time and permanent increase in efficiency subsequent to both market reforms and improved trading practices in the Indian stock market. The results are robust to alternate time domain and frequency domain measures of Hurst exponent.